2016
DOI: 10.2147/ijn.s94255
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia treatment of tumors by mesenchymal stem cell-delivered superparamagnetic iron oxide nanoparticles

Abstract: Magnetic hyperthermia – a potential cancer treatment in which superparamagnetic iron oxide nanoparticles (SPIONs) are made to resonantly respond to an alternating magnetic field (AMF) and thereby produce heat – is of significant current interest. We have previously shown that mesenchymal stem cells (MSCs) can be labeled with SPIONs with no effect on cell proliferation or survival and that within an hour of systemic administration, they migrate to and integrate into tumors in vivo. Here, we report on some longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 54 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…Kalber et al reported migration and integration of systemically administered SPION-labeled MSCs in ovarian tumor nude mouse model. 3 They found that even though the nanocarrier was able to accumulate into tumors, the amount of magnetic nanoparticles was not necessarily enough to promote hyperthermia in order to treat cancer exclusively by heat delivery 14 days after the administration of labeled MSCs. Studies of biodistribution, migration, and homing of systemically applied MSCs revealed that 80% of cells are immediately entrapped in the lung tissue and then cleared to the liver within 1 day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalber et al reported migration and integration of systemically administered SPION-labeled MSCs in ovarian tumor nude mouse model. 3 They found that even though the nanocarrier was able to accumulate into tumors, the amount of magnetic nanoparticles was not necessarily enough to promote hyperthermia in order to treat cancer exclusively by heat delivery 14 days after the administration of labeled MSCs. Studies of biodistribution, migration, and homing of systemically applied MSCs revealed that 80% of cells are immediately entrapped in the lung tissue and then cleared to the liver within 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] This approach involves targeting magnetic nanoparticles to tumors and then inducing cytotoxic hyperthermia by applying an alternating magnetic field (AMF). Iron oxide nanoparticles are optimal for inducing hyperthermia, and their effectiveness as a cancer therapeutic should be evaluated according to the following criteria: 1) they should selectively target tumor cells, 2) they should easily penetrate tumor cells, 3) they should be internalized by tumor cells, 4) they should be biocompatible and nontoxic across a wide range of concentrations, 5) they should be easy to administer in the clinic, 6) they should be likely to be approved for clinical use, and 7) they should be targetable to specific tumor types or to organs with metastases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminosilane-coated iron oxide (NanoTherm), significantly polarized under external magnetic fields to selectively ablate tumors by heat generation, is undergoing clinical trials in the USA [118-120]. FDA-approved SPIONs were also found to inhibit tumor growth by hyperthermia under magnetic fields at preclinical levels [121-123]. The integration of multiple energies and modalities is a unique characteristic of nanoparticles that will make them invaluable for detection and therapy in a wide variety of diseases.…”
Section: Therapymentioning
confidence: 99%
“…15,16 The superiority of MRI in tracking and monitoring transplanted stem cells has been established using different cell types, such as bone mesenchymal stem cells (BMSCs), peripheral blood stem cells, and embryonic stem cells. 17 Superparamagnetic iron oxide (SPIO) nanoparticles are the most sensitive MRI contrast agents used in cell labeling. They are safe and biodegradable, and they do not affect the proliferation and differentiation capacity of implanted cells in vitro and in vivo.…”
Section: Zheng Et Almentioning
confidence: 99%